Precision cancer medicine: What has translated into clinical use in Belgium?. (September 2022) - Delnord, M.; Van Valckenborgh, Els; Hebrant, Aline; Antoniou, Aline; Van Hoof, Wannes; Waeytens, Anouk; Van den Bulcke, M.
Abstract: Rationale: In 2016, Belgium launched the Next Generation Sequencing (NGS) Roadbook, consisting in 10 Actions, across the health care system, to facilitate the uptake of NGS in routine clinical practice. We compiled feedback on deployment of the NGS Roadbook from governmental stakeholders and beneficiaries: health policy makers, insurance providers, pathologists, geneticists, and oncologists. Main findings: The Roadbook ensured the establishment of a Commission on Personalized Medicine and NGS testing guidelines. A national benchmarking trial ensued, and 10 networks of hospitals and laboratories adopted a reimbursement convention with the Belgian Health Insurance Agency. The Healthdata.be platform centralizes the collection of NGS metrics, and citizens were consulted on their views about NGS and genomics. Conclusion: The Roadbook facilitated the implementation of NGS in routine (hemato-)oncology care in Belgium. Some challenges remain linked to data sharing and access by a wider range of stakeholders. Next steps include continuous monitoring of health outcomes and the budgetary impact.